2014
DOI: 10.1371/journal.pone.0104744
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Pedagogy: An Effective Approach to Cater for Individual Differences in Learning a Sports Skill

Abstract: Learning a sports skill is a complex process in which practitioners are challenged to cater for individual differences. The main purpose of this study was to explore the effectiveness of a Nonlinear Pedagogy approach for learning a sports skill. Twenty-four 10-year-old females participated in a 4-week intervention involving either a Nonlinear Pedagogy (i.e.,manipulation of task constraints including equipment and rules) or a Linear Pedagogy (i.e., prescriptive, repetitive drills) approach to learn a tennis for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
125
0
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(146 citation statements)
references
References 39 publications
7
125
0
14
Order By: Relevance
“…The shuttlecock has an typical trajectory and the players perform specific movements such as lunging and jumping, and powerful strokes using a specific pattern of movement. Badminton players should be visually fit, picking up accurate visual information in a short time [33] In another study by Lee, Chow, Komar, Tan, and Button [17] …”
Section: Teachers Inputmentioning
confidence: 99%
“…The shuttlecock has an typical trajectory and the players perform specific movements such as lunging and jumping, and powerful strokes using a specific pattern of movement. Badminton players should be visually fit, picking up accurate visual information in a short time [33] In another study by Lee, Chow, Komar, Tan, and Button [17] …”
Section: Teachers Inputmentioning
confidence: 99%
“…The NLP pedagogical principle of self-organisation under constraints challenges the misconception that there is one common optimal movement solution for a task towards which all learners should aspire. This principle is predicated on the inherent adaptive movement variability and degeneracy of human movement systems, that is, learners have the ability to self-organise in many different ways to achieve the same outcome or task goal (Davids, Button, and Bennett 2008;Lee et al 2014). Degeneracy is important in skill acquisition as it empowers the individual with a variety of movement possibilities or solutions that may be exploited to fulfill the demands of the task and a dynamic environment (Chow et al 2008;Lee et al 2014).…”
Section: Nlp and Sdtmentioning
confidence: 99%
“…This principle is predicated on the inherent adaptive movement variability and degeneracy of human movement systems, that is, learners have the ability to self-organise in many different ways to achieve the same outcome or task goal (Davids, Button, and Bennett 2008;Lee et al 2014). Degeneracy is important in skill acquisition as it empowers the individual with a variety of movement possibilities or solutions that may be exploited to fulfill the demands of the task and a dynamic environment (Chow et al 2008;Lee et al 2014). According to Renshaw, Oldham, and Bawden (2012), adopting this NLP principle of self-organisation under constraints in practice can also meet the psychological needs of the individual performer by enhancing learners' perceptions of autonomy and competence.…”
Section: Nlp and Sdtmentioning
confidence: 99%
“…For instance, recent investigations on nonlinear pedagogy (e.g. Komar, Chow, Chollet, & Seifert, 2014;Lee, et al, 2014) have shown that promoting intra-individual variability during practice is likely to favour inter-individual variability in movement patterns after many weeks of practice, therefore respecting the individual constraints acting on each performer. For both researchers and practitioners, it might be well to reconsider the research methodology in movement science and to complete the traditional linear analysis of the amount of variability with analytic techniques that provide access to the embedded structure of movement variability.…”
Section: Resultsmentioning
confidence: 99%